СПОСОБИ ЗАХИСТУ ПОРУШЕНИХ ПРАВ НА ТЕХНОЛОГІЮ: ЦИВІЛЬНО-ПРАВОВИЙ І ГОСПОДАРСЬКО-ПРАВОВИЙ АСПЕКТИ - Rozghon, Olha (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2024)
The article examines technology as an object of legal regulation and highlights the ways of protecting violated rights to technology. The article examines technology as an object of legal regulation and identifies the ways to protect infringed rights to technology. The novelty of the work lies in the author's identification of the specifics of the ways to protect infringed rights to technology within the framework of Civil and Economic law. The author proves that the concept of “technology” is widely used in the literature, but there are significant differences of opinion among scholars regarding its essence. The research has led to the conclusion that technology can be considered as an object of Civil and Economic law relations. The author points out that technology is not an object of intellectual property rights, since an exhaustive list of intellectual property objects is provided in Article 420 of the Civil Code of Ukraine. However, the author notes that the object of technology may be objects of intellectual property rights (in particular, industrial property rights). It is determined that fixation and mediation of relations of an innovative nature by concluding a technology transfer agreement with certain conditions and requirements are necessary to ensure additional legal protection of the parties to a technology transfer agreement. The article emphasizes that the process of technology transfer and its transferred components are necessarily formalized through the conclusion of a technology transfer agreement. The author notes that since the essential terms of a technology transfer agreement include the parties' liability for breach of the agreement and the procedure for resolving disputes regarding the fulfillment of the agreement, in case of breach of the agreement, general remedies may be applied to protect the parties to contractual relations in the field of technology transfer. Moreover, within the framework of civil law relations, the most popular will be compensation for damages due to non-performance or improper performance of a technology transfer agreement. The author emphasizes that technology is an object of legal regulation, its individual components have the legal status of other objects of Civil law regulation, and therefore, in case of infringement of intellectual property rights to technology, both general and special remedies for protection of rights to technology are applicable.